Does the Glass Ceiling Exist? A Cross-National Perspective on - Ira N. Gang; John S. Landon-Lane; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2003)
We compare male and female upward labor income mobility in Germany and the United States using the GSOEP-PSID Cross National Equivalent File. Our main interest is to test whether a glass ceiling exists for women. The standard glass ceiling hypothesis highlights the belief that the playing field is level for women and men in the labor market up to a point, after which there is an effective limit on advancement for women. We examine the glass ceiling hypothesis by looking at the dynamics of the income distribution – the movement of women and men through the distribution of income over time. We find that there is considerable evidence in favor of a glass ceiling both in Germany and the United States. In Germany the glass ceiling is evident in higher incomes while in the United States the glass ceiling is evident at all incomes levels.
Keywords: J7; D3; D63; 330; glass ceiling; mobility; Markov chain; income distribution dynamics; gender; Frauenarbeitslohn; Erwerbsverlauf; Lohndifferenzierung; Soziale Mobilität; Geschlecht; Schätzung; Vereinigte Staaten; Deutschland